Mr. Manning's Proposition to pay off (Quarterly Journal of Economics, 1887)
Journal Article Mr. Manning's Proposition to pay off Get access The Quarterly Journal of Economics, Volume 1, Issue 2, January 1887, Pages 223–224, https://doi.org/10.1093/qje/1.2.223-c Published: 01 January 1887